South Pole Lake GNSS - Hills, Benjamin (IEDA: US Antarctic Program Data Center, 2021)
These are ground-based GNSS data collected from a subglacial lake ~15 km from the geographic South Pole. Data were collected with two separate antenna/receiver systems: 1) Septentrio Altus APS3G antenna/receiver 2) Trimble NetR8 and Trimble Zephyr Geodetic antenna.